Knowledge Management Implementation Model for Community Information service (CIS) in the library: A case of Penang State Library - Shukriah, Yon (Universiti Malaysia Perlis (UniMAP), 2010)
International Conference On Libraries (ICOL) 2007, 31st October - 2nd November 2007 organized by Universiti Sains Malaysia (USM) with the coorperation of Librarians Association of Malaysia at Gurney Hotel, Penang.